Mechanisms of collateral damage: heterospecific neighbor density mediates parasitism by eavesdroppers on hourglass treefrogs. Issue 5 (3rd September 2022) - Ruether, Brian F.; Brady, Meghan J.; Derick, Taylor L.; Dula, Brendan T.; Smith, Sarah A.R.; Trillo, Paula A.
Abstract : Males often broadcast conspicuous signals from within mixed-species aggregations to attract mates. In addition to attracting females, however, these displays expose signalers to eavesdropping predators and parasites. For individuals in mixed-species aggregations, the balance between attracting mates and avoiding eavesdroppers is influenced both by the attractiveness of their calls and by the calling activity of conspecific and heterospecific neighbors. Through a process termed "collateral damage", frogs signaling near heterospecific neighbors that are highly attractive to eavesdroppers can experience drastically increased parasitism compared to those signaling next to conspecifics. Here, we investigate whether the intensity of this collateral damage is influenced by the density of, or the call types produced by, heterospecific neighbors. In phonotaxis trials using hourglass treefrogs as the focal species and túngara frogs as the attractive heterospecific neighbor, we found no differences in the number of parasites attracted to hourglass treefrog calls played adjacent to simple versus complex túngara calls. By contrast, a higher density of neighboring túngara frogs decreased the collateral damage suffered by hourglass treefrogs by approximately 40%. Our results demonstrate that the density of nearby heterospecifics can modulate parasitism risk due to collateral damage in mixed-species aggregations. Thus, our conception of the dilution of eavesdropper risks with increasing group size may need to be augmented to include the effects of multiple prey or host types. HIGHLIGHTS ● Heterospecific call type does not change collateral damage on hourglass treefrogs ● However, parasitism decreases when calling next to high densities of heterospecifics